Application of deep dehumidification technology in low-humidity industry : A review - Zhang, Qunli; Li, Yanxin; Zhang, Qiuyue; Ma, Fengge; Lü, Xiaoshu (Elsevier, 2024)
Humidity regulation plays a pivotal role in both residential and industrial environments, significantly impacting comfort, health, and process efficiency. The integration of dehumidification systems with air conditioning systems allows for the control of temperature and humidity, resulting in a decrease in carbon dioxide emissions. In order to address the demands of industries with low humidity levels, this study offers a comprehensive review of advanced deep dehumidification systems. The study initially delineates the specific ranges for deep dehumidification as outlined in academic research, as well as the humidity levels in low-humidity industries. Evaluation models are proposed for the analysis of the dehumidification performance, energy efficiency, economic feasibility, and environmental impact of the system. The review focuses on the deep dehumidification technology, which encompasses air compression dehumidification, liquid desiccant dehumidification, solid desiccant dehumidification, membrane dehumidification, and coupled dehumidification, with an emphasis on materials, components, and systems flow. The research provides a comprehensive overview of the various potential applications of dehumidification systems, including air humidification, water collection, air purification, intelligent control, and optimization. Moreover, a comprehensive comparative analysis of different dehumidification technologies is conducted with regard to industrial application humidity requirements, energy performance, economic factors, and environmental considerations. Drawing on advanced studies and findings, this research examines the primary areas for future development in advancing deep dehumidification systems. The objective of this study is to propose optimization techniques aimed at enhancing dehumidification efficiency and reducing energy consumption in low-humidity industrial settings.
Keywords: Air humidity; Deep dehumidificatio; Desiccant; Dew point temperature; Review; energy consumption (energy technology); fi=Energiatekniikka|en=Energy Technology|